Vermicomposting for household and modern gardeners / Wan Hanisah Wan Ismail - Wan Ismail, Wan Hanisah (2006)
Vermicomposting as a method of solid waste management alternative is gaining increasing consideration by most environmentalists around the world. Started by farmers in the temperate countries to decompose their solid waste particularly during the winter seasons, vermicomposting has become a common trend of solid waste management in most of the developed countries. However, this technology is quite new to the Third World particularly the Asian countries where the climatic and environmental conditions are quite different from those of the developed countries. This paper introduces some of the basics of vermicomposting, its benefits. the current situation as well as its commercial potential in the management of other waste and environmental preservation